The association between hypertension and diabetes in a Family Health Center - Daniele Braz da Silva; Tereza Alves de Souza; Célia Maria dos Santos; Mércia Marques Jucá; Thereza Maria Magalhães Moreira; Mirna Albuquerque Frota; Silvânia Maria Mendes Vasconcelos (Universidade de Fortaleza, 2011)
Objective: To describe the clinical characteristics of patients with hypertension treated in a health unit and its association with diabetes, relating to sex and age. Methods: We conducted this quantitative and documentary research with 297 registered users in the Plan of Reorganization of Care for Hypertension and Diabetes Mellitus (HIPERDIA / MS) of a Family Health Center of the Regional Executive Office VI (SER VI) at Fortaleza -Ceará, in May 2009. The sample was divided according to gender, age and relationship betweenhypertension and diabetes. Results: We found a predominance of women, over 40 years, with hypertension and without diabetes. Fifty-eight (19.5%) users had hypertension and diabetes associated, suggesting an additional risk factor, relevant to this clientele. One hundredand fifty-five (52.2%) of hypertensive patients, with and without diabetes, controlled blood pressure and among those who were not in control, 85 (28.6%) were elderly. It was identified that 46 (15.5%) users were affected by some complication, especially the stroke as the most prevalent among female 13 (52%) and acute myocardial infarction in male 11 (38%). The antihypertensive drugs and hypoglycemic most used were 170 (71.1%) hydrochlorothiazide,44 (75.9%) glibenclamide and 04 (6.9%) insulin. Conclusion: High blood pressure affects men and women, and its prevalence increases with age. When associated with diabetes, increases the risk of developing cardiovascular disease. It is believed that the education of individuals with chronic illness is the best way to reduce these harms.